2022
DOI: 10.3389/fenvs.2022.899727
|View full text |Cite
|
Sign up to set email alerts
|

Response of Soil Microbial Community Structure to Phosphate Fertilizer Reduction and Combinations of Microbial Fertilizer

Abstract: The excessive application of phosphorus (P) fertilizer is becoming a major agricultural problem, which reduces the utilization rate of the P fertilizer and degrades soil quality. The following five P fertilizer treatments were investigated to know how they affect soil properties, enzyme activity, bacterial and fungal community structure. 1) no P fertilizer (P0); 2) farmers’ traditional P fertilization scheme (FP); 3) 30% reduction in P fertilizer application (P1, microbial blended fertilizer as base fertilizer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 47 publications
(48 reference statements)
0
13
0
Order By: Relevance
“…Soil P availability has been reported to influence the structure of soil microbial communities, as well as the corresponding functions and metabolisms ( Liu et al., 2022 ; Wu et al., 2023 ). Consequently, different fertilization regimes exert different effects on microbial life strategies, shaping soil P cycling processes ( Fierer et al., 2007 ; Bergkemper et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Soil P availability has been reported to influence the structure of soil microbial communities, as well as the corresponding functions and metabolisms ( Liu et al., 2022 ; Wu et al., 2023 ). Consequently, different fertilization regimes exert different effects on microbial life strategies, shaping soil P cycling processes ( Fierer et al., 2007 ; Bergkemper et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorus (P) is an essential macronutrient for plants, playing a crucial role in the synthesis of nucleic acids, enzymes, and coenzymes ( Mehnaz et al., 2019 ). However, P utilization in agroecosystems is always inefficient (10%–20%), making P a major limiting nutrient in agriculture ( Pantigoso et al., 2020 ; Liu et al., 2022 ). After being applied to soils, P fertilizers are easily absorbed and fixed, thus the P is inaccessible to plants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, evidence showed that high pH and high AP content could reduce the abundances of taxa with genes encoding phoD such as Gemmatales , since we found a negative correlation between AP and Gemmatales . Nodes belonging to Acidobacteriales had an opposite correlation with AP and AP-related taxa, indicating that different specific taxa belonging to Acidobacteriales might play different roles in phosphorus metabolism ( Cui et al, 2022 ; Liu H. et al, 2022 ). Strong correlations were found between Polyangiales and AP ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, decreased P availability is a critical factor for the declining productivity in saline-alkali soils (Huang et al, 2022). Microbial fertilizers and inorganic materials are often used to activate immobilized inorganic P with phosphate fertilizer applications, which increases the labor input (Liu et al, 2022;Xu et al, 2016). Thus, it is imperative that effective methods to improve P availability are researched under salinization conditions (Wagdi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%